Evaluation of The Role of Social Capital in the Tea Farmer Partnership System at PT. Pagilaran Afdeling Samigaluh Kulon Progo - Resna Trimerani; Fani Ardiani (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2023)
Partnership is a form of cooperation that exists between two parties, where the relationship provides benefits to each other. Partnership cooperation is generally agreed in writing and includes clear rights and obligations between both parties. The commitment that occurs between both parties is the main key in the parthership system. In addition, the role of social capital in the form of trust, norms and social networks is also needed to support the sustainability of partnership, in this case tea farmers and PT. Pagilaran. This research aims to determine the tea farmer partnership system at PT. Pagilaran Afgdeling Samigaluh and find out the role of social capital in the tea farmer partnership system at PT. Pagilaran Afdeling Samigaluh. The method used in this reseach are survey and descriptive with a qualitative approach. The research results show that the partnership system thah exists between tea farmers and PT. Pagilaran Afdeling Samigaluh is a pure partnership system (buy and drop). Apart of that, social capital in the form of trust, norms and social networks in the partnership system between tea farmers and PT. Pagilaran Afdeling Samigaluh plays a very important role in maintaining the sustainability of the partnership and of course still pays attention to the rights and obligations of each parties.